2016
DOI: 10.5694/mja16.00069
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Composite reliability of workplace‐based assessment for international medical graduates

Abstract: WBA is a reliable method for assessing IMGs when multiple tools and assessors are used over a period of time. This form of assessment meets the criteria for "good assessment" (reliability ≥ 0.8) and can be applied in other settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…A previous study assessing the composite reliability of WBA, found that it is a reliable assessment. 12 …”
Section: Methodsmentioning
confidence: 99%
“…A previous study assessing the composite reliability of WBA, found that it is a reliable assessment. 12 …”
Section: Methodsmentioning
confidence: 99%